The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0045118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sigma-1 Receptor Agonist 1-(3,4-Dimethoxyphenethyl)-4-(3-Phenylpropyl)-Piperazine Dihydro-Chloride on Inflammation after Stroke

Abstract: Activation of the sigma-1 receptor (Sig-1R) improves functional recovery in models of experimental stroke and is known to modulate microglia function. The present study was conducted to investigate if Sig-1R activation after experimental stroke affects mediators of the inflammatory response in the ischemic hemisphere. Male Wistar rats were subjected to transient occlusion of the middle cerebral artery (MCAO) and injected with the specific Sig-1R agonist 1-(3,4-dimethoxyphenethyl)-4-(3-phenylpropyl)piperazine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…In addition, in models of rheumatoid arthritis and sepsis, a decrease in cytokine release was observed after treatment with the r ligands SR31747A and SSR 125329A, respectively. 39,40 However, Ruscher et al 28 have found that exposure of rat brain-derived microglia to the rR1 ligand SA4503 did not affect the release of proinflammatory mediators after combined hypoxia/aglycemia stimulation. To our knowledge, no previous reports address the effects of (þ)-pentazocine, specifically, on microglia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in models of rheumatoid arthritis and sepsis, a decrease in cytokine release was observed after treatment with the r ligands SR31747A and SSR 125329A, respectively. 39,40 However, Ruscher et al 28 have found that exposure of rat brain-derived microglia to the rR1 ligand SA4503 did not affect the release of proinflammatory mediators after combined hypoxia/aglycemia stimulation. To our knowledge, no previous reports address the effects of (þ)-pentazocine, specifically, on microglia.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition to neuroprotection, rR1 activation has been associated with decreased reactive gliosis in both the ALS mouse model and the rat stroke injury model. 26,28 Evidence also suggests that some rR1 ligands can repress activation of the MAPK/ERK pathway within cortical neurons. 29 Recent work has shown that r receptors modulate the activation of CNS-derived primary microglia.…”
mentioning
confidence: 99%
“…Following cerebral ischemia, both necrotic and apoptotic cell death can be induced through complex interactions of pathological processes, including excitotoxicity and inflammation [8, 9]. Neuroprotective and neurorestorative effects of sigma-1 agonists (e.g., decreasing cell death, protecting against tissue damage, and increasing synaptic protein expression) have been shown in multiple animal models of stroke, including mouse [10], rat [1116], gerbil [17] and cat [18]. In rat models of stroke, for example, decreased infarct volume as well as enhanced neuronal survival were observed following acute treatment with a sigma agonist 24 h after the onset of ischemia [14, 15].…”
Section: 2 Sigma-1 Receptor Ligands In Animal Models Of Neurodegenmentioning
confidence: 99%
“…The significant down-regulation of IL13 in soy-fed rats was an unexpected result, as IL13 is traditionally considered an antiinflammatory cytokine. Previous studies revealed both increases (Ruscher et al, 2012) and decreases (Yu et al, 2010) in IL13 in response to ischemia, although the latter result reflects hippocampal injury in Mongolian gerbils. The lack of IL13 increase in the soy-fed animals may be interpreted as either a reduction of injury that fails to reach the threshold for IL13 activation or a reduction in potential deleterious effects of IL13.…”
Section: Discussionmentioning
confidence: 81%